Energy Applications in Green Building to Fulfil the Goals of Sustainable Development: The Case of Jordan - Albaali, Abdul Ghani; Shahateet, Mohammed Issa (International Journal of Energy Economics and Policy, 2022)
The aim of this study is to explore measures and options for utilizing the most abundant energy source in Jordan, which is solar energy. The study looks into the actions that Jordan can adopt that will give the stakeholders a higher return on investment. It emphasizes the importance of using such facilities in the applications of green building, which is growing in the country. The methodology is descriptive and analytical, using official data to support these options, such as the price of labor, land, oil, as well as equipment that is used in the building of energy infrastructure. The importance of the options stems from the fact that they minimize the energy gaps to form a thorough policy for any organization or ministry in the government. The study showed that the payback period for the installation of both solar water collectors and solar cell panels is approximately 2 and 2.5 years, respectively. This study has also arrived at several actions and recommendations to shrink the energy gap. The disparity between subsidies for low-energy users and high-energy users has slowed the development of alternative energies. Other kinds of renewable energy, such as hydroelectric and wind power, are underutilized in Jordan, although they can be utilized to reduce the volatility of oil and gas prices.